Management of Burn Wounds - Schiestl, Clemens; Meuli, Martin; Trop, Marija; Neuhaus, Kathrin (European Journal of Pediatric Surgery, 2013)
Small and moderate scalds in toddlers are still the most frequent thermal injuries the pediatric surgeons have to face today. Over the last years, surgical treatment of these patients has changed in many aspects. Due to new dressing materials and new surgical treatment strategies that are particularly suitable for children, today, far better functional and aesthetic long-term results are possible. While small and moderate thermal injuries can be treated in most European pediatric surgical departments, the severely burned child must be transferred to a specialized, ideally pediatric, burn center, where a well-trained multidisciplinary team under the leadership of a (ideally pediatric) burn surgeon cares for these highly demanding patients. In future, tissue engineered full thickness skin analogues will most likely play an important role, in pediatric burn as well as postburn reconstructive surgery.
Keywords: burns; scalds; child; toxic shock syndrome; tissue engineering